2021
DOI: 10.1002/mmce.22630
|View full text |Cite
|
Sign up to set email alerts
|

A radio frequency energy harvesting rectenna for GSM , LTE , WLAN, and WiMAX

Abstract: A new multiband circular polarized rectenna is implemented as a radio frequency (RF) power harvesting system tuned for the quad bands of 1.8 GHz (GSM 1800), 2.4/5.8 GHz (WLAN), and 3.6 GHz (WiMAX). An innovative monopole antenna is made for the rectenna; consisting of an octagonal shaped microstrip patch, loaded with an I-shaped rectangular slot and three L-shaped stubs so that the antenna creates circular polarization at the quad bands. The second part of the rectenna is a multi-frequency impedance matching n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In Addepalli et al, 21 the suggested antenna offers a significantly smaller bandwidth, and the isolation between antenna elements is below −15 dB, which is relatively low compared to the proposed antenna. In Mirzababaee et al, 23 the antenna does not show MIMO characteristics and reconfigurability. The antenna size is enormous in Takhedmit et al 32 and Haboubi et al, 33 and the harvested output voltage is 150 and 189 mV at −15 dBm, which is quite low than the proposed work.…”
Section: Description Of the Antennamentioning
confidence: 95%
See 2 more Smart Citations
“…In Addepalli et al, 21 the suggested antenna offers a significantly smaller bandwidth, and the isolation between antenna elements is below −15 dB, which is relatively low compared to the proposed antenna. In Mirzababaee et al, 23 the antenna does not show MIMO characteristics and reconfigurability. The antenna size is enormous in Takhedmit et al 32 and Haboubi et al, 33 and the harvested output voltage is 150 and 189 mV at −15 dBm, which is quite low than the proposed work.…”
Section: Description Of the Antennamentioning
confidence: 95%
“…Conversely, numerous devices and sensors rely on rechargeable batteries for power, often situated in remote locations. Consequently, ambient RF energy harvesting might be an acceptable replacement for such devices to avoid the replacement of the battery while also lowering expenses 23–28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[72] A high PCE value is preferable, but it is limited by power losses due to leakage currents and parasitic RLC components, which are unavoidable in real-life applications. Recent articles investigating the maximum power conversion efficiency of EH/PT rectennas report the highest PCE values above 60% [73][74][75] with a peak value of 85% [76] using conventional PCB technology.…”
Section: Rectenna Design and Efficiency In Eh And Wpt System Designmentioning
confidence: 99%
“…The IMN adjusts the impedance between the receiving antenna and the rectifier circuit. In the absence of IMN, all the energy received by the system will be reflected, causing a decreased amount of rectified output current obtained by the load [15]. The RF signals are then transferred from the IMN to the rectifier circuit for radio frequency waves to direct current (RF-DC) conversion, before being supplied to the load.…”
Section: Introductionmentioning
confidence: 99%